One-step gas-phase syntheses of few-layered single-phase Ti2NCl2 and Ti2CCl2 MXenes with high stabilities - Fen Yue; Maoqiao Xiang; Jie Zheng; Jiuyi Zhu; Jiake Wei; Puheng Yang; Hebang Shi; Qinghua Dong; Wenjun Ding; Chenchen Chen; Yafeng Yang; Chuanfang John Zhang; et al. (Nature Communications)
Abstract With the iteration of etching techniques, MXenes have exhibited astounding accomplishments. Nevertheless, intricate procedures, expensive precursors, and degradation present obstacles for practical application. Although chemical vapor deposition has been developed as a solution, direct syntheses of few-layered single-phase MXenes remain an open challenge, especially for Ti2NCl2. Here, we propose a one-step gas-phase synthetic method to fabricate few-layered single-phase Ti2NCl2 and Ti2CCl2. Design of the activation section and segregation from the synthetic zone are the key factors. The reaction paths, synthetic mechanism, and degradation behavior are revealed. Due to the low proportion of Ti vacancies, the time constant of the Ti2CCl2 solution is 73 times longer than that of Ti2CCl x . Furthermore, the specific capacity for Li+ storage with Ti2NCl2 is 1.37 times greater than that of Ti2CCl2. The one-step gas-phase method will accelerate practical application of MXenes.